Analisis Pola Aliran Dan Pola Sedimentasi Pada Waduk Sei Paku Kecamatan Kampar Kiri Kabupaten Kampar - Freester, Joy; Mudjiatko, Mudjiatko; Sujatmoko, Bambang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The non-uniformity topography of Sei Paku Reservoir caused non-uniform flow in the reservoir, forming unique flow pattern. This flow pattern caused the uneven of flow velocity distribution and sediment distribution in the reservoir. The uneven of flow velocity distribution and sediment distribution can affect the trend of bed configuration changes of the reservoir. It takes a form of a simulation study to determine the pattern and flow velocity distribution, and sediment distribution in the reservoir. In the simulation, topography data, flood discharge, and the water level are processed by RMA-2 that produces flow patterns and the flow velocity. Parameters such as sediment grain size and sediment concentrations are processed by SED2D that produces sediment distribution. The simulation results showed that the flow patterns affect the flow velocity distribution and the sediment distribution in the reservoir so that happen bed configuration changes of the reservoir. The bed configuration of Sei Paku reservoir classified by simulation results in “Anti Dunes” phase where upstream side suffered deposition while downstream side suffered erosion.Keyword: Simulation, flow pattern, sedimentation